Кто же мы? - Мегре Владимир Николаевич (2001)
На тит. л. и обл. только частное загл. тома Экземпляры: ф.1 (2003) / Инвентарный номер: 44953 / Цена: / Сис.шифр: 86.42 / Авт.знак: М 41 / ГРНТИ: 21.15.69 / ББК: 86.42